Creative Class in Türkiye: New Job Prospects - Skavronska, Iryna (Technium Social Sciences Journal, 2023)
This paper covers a comprehensive study of the creative class in Türkiye in terms of new job prospects. Nowadays, creativity is one of key skills necessary for future jobs. People, who have creative and innovative thinking, generate original ideas and produce unique products, form a special stratum of society called creative class. Creative class professionals include scientists, teachers, artists, models, social media influencers, etc. This article is intended to outline the specifics of new type of workers’ lifestyle which implies comfortable living conditions known as “quality of place.” In order to clarify how ready Türkiye is for the development of the creative class, the state of the labor market is analyzed. It has been revealed that the Turkish labor market is characterized by both strengths (e.g. large population, a large share of the youth, increase in labor productivity) and weaknesses (e.g. labor underutilization, limited female labor participation, lack of skills). People mainly work in agriculture, industry, service sector and construction. These characteristics outline the basis for the rise of the creative class and the emergence of new careers in Türkiye. Correspondingly, this research is aimed at analysis and assessment of factors, circumstances and preconditions for the emergence of the creative class in Türkiye as well as determining the creative class job opportunities. The methodology of the study is founded on exploring new and potential jobs that will be required by the future. The article presents a framework for the assessment of the creative class in Türkiye based on the standard measures of job quantity, as well as job quality and labor market inclusiveness. The paper proposes the vision of how Türkiye can drive talent transformation and upskill its workforce in order to satisfy demand for innovative type of workers and take advantage of new opportunity. This study provides a unique and vital contribution to ongoing discussions about the significance of the creative class for employment highlighting the universalized assumptions concerning the position of these professionals in the Turkish economy.